Regulatory effects of differential dietary energy levels on spermatogenesis and sperm motility of yellow-feathered breeder cocks - Xue, Fuguang; Liu, Yifan; Lv, Ziyang; Zhang, Jian; Xiong, Shiyuan; Zha, Liqing; Liu, Zhiyu; Shu, Jingting (Frontiers in Veterinary Science, 2022)
The semen quality of breeder cocks profoundly impacted the numbers of matched layer hens and the economic benefits of the poultry industry. Adequacy and balance of poultry nutrition, especially the energy provision, critically modulated the reproductive potential of breeder cocks, however, the underlying mechanism was still unclear. For the purpose of this study, a total of 90 yellow-feathered 13-week-old roosters with the same age in days and similar body weight (1,437 ± 44.3 g) were selected and randomly divided into the low energy diet (LE), the moderate energy diet (ME), and the high energy diet (HE) treatments. The phenotypic parameters related to reproduction include semen quality, fertility, and hatchability, and the testis morphological parameters, including seminiferous epithelium length (SEL), seminiferous tubule perimeter (STP), seminiferous tubule area (STA), and Johnsen score, were measured to investigate the regulatory effects of different energy diets on reproductive performances. Furthermore, spermatogenesis and sperm motility-related genes, which included the sry-related high mobility group box (SOX) gene family and sperm-associated antigen (SPAG) gene family, and mitochondria apoptosis-related genes, such as Cyt-C, Bcl-2, and Bax, were measured to determine the underlying mechanism of energy on the reproductive performances. The The results showed that the gonadosomatic index and sperm motility in the ME treatment significantly increased compared with the LE treatment. Chickens in the ME treatment showed a preferable performance of testis development, especially a significant increment of SEL and Johnsen Score, compared with the LE and HE treatments. Finally, spermatogenesis-related genes, which included SPAG6, SPAG16, SOX5, SOX6, and SOX13, and apoptosis-related genes of mitochondria, such as the Cyt-C and Bcl-2, were significantly upregulated in the ME treatment. This study concluded that proper energy provision stimulated regular energy metabolism for spermatogenesis and sperm capacitation, which finally increased semen quality and reproductive performances of breeder cocks.